A taxonomy of financial crisis resolution mechanisms : cross-country experience - Calomiris, Charles W., 1957- 1957- (Policy research working paper, 2004)
"The goals of financial restructuring are to reestablish the creditor-debtor relationships on which the economy depends for an efficient allocation of capital, and to accomplish that objective at minimal cost. Costs include direct costs to taxpayers of financial assistance and the indirect costs to the economy that result from misallocations of capital and incentive problems resulting from the restructuring. Calomiris, Klingebiel, and Laeven review cases in which countries used alternative mechanisms to restructure their financial and corporate sectors. Countries typically apply a combination of tools, including decentralized, market-based mechanisms, and government-managed programs. Market-based strategies seek to strengthen the capital base of financial institutions and borrowers to enable them to renegotiate debt and resume new credit supply. Government-led restructuring strategies often include the establishment of an entity to which nonperforming loans are transferred or the government's sale of financial institutions, sometimes to foreign entrants. Market-based mechanisms can, in principle, resolve coordination problems that countries face in the wake of massive debtor and creditor insolvency, with acceptably low direct and indirect costs, particularly when those mechanisms are effective in achieving the desirable objective of selectivity. However, these mechanisms depend for their success on an efficient judicial system, a credible supervisory framework and authority with sufficient enforcement capacity, and a lack of corruption in implementation.